Graphene oxide and its derivatives as potential Ovchinnikov ferromagnets. (9th July 2021) - Sinha, Apurva; Ranjan, Pranay; Ali, Anzar; Balakrishnan, Jayakumar; Thakur, Ajay D
Abstract: Ovchinnikov postulated the possibility of ferromagnetism in organic compounds having a mixed density of sp 3 and sp 2 carbon atoms. Such systems provide an interesting avenue for exploring magnetism in the absence of the quintessential d - and f -block elements as ingredients. As graphene oxide (GO) and its derivatives naturally possess a mixture of sp 3 and sp 2 carbon atoms, it is pertinent to look at them as potential candidates for Ovchinnikov ferromagnetism. We have looked at the evolution of magnetic property in a series of GO samples with a gradual increase in the degree of oxidation and hence the sp 3 / sp 2 fraction. Starting with a GO sample with a high sp 3 / sp 2 ratio, we utilize chemical reduction technique to prepare another set of reduced graphene oxide (rGO) samples. Magnetization measurements on these samples further illustrate the importance of sp 3 / sp 2 fraction on magnetic behavior suggesting GO and its derivatives as a potential Ovchinnikov ferromagnet candidate. The evolution of magnetic moment with sp 3 / sp 2 carbons can be utilized in carbon based spintronic applications.